Inter-communal Violence in sub-Saharan Africa: the Role of Corporate Social Responsibility in Nigeria's Oil Producing Region - Joseph Ikechukwu Uduji; Elda Nduka Okolo-Obasi; Justitia Odinakachukwu Nnabuko; Geraldine Egondu Ugwuonah; Josaphat Uchechukwu Joe Onwumere (African Governance and Development Institute (AGDI), 2024)
We examine the impact of multinational oil companies' (MOCs) corporate social responsibility (CSR) using global memorandum of understanding (GMoU) on mitigating the resurgence of intercommunal violence in Niger Delta, Nigeria. Using explanatory research design, the study adopted mixed methods to answer the research questions and test the hypotheses of the study. Primary data were generated from a sample of 1200 respondents selected form all the nine states of the region using multiple sampling techniques. We carried out both survey with structured questionnaire and key informant interview to ascertain the effect of CSR on the resurgence of inter-communal violence in the region. Results from the use of a logit model and use of propensity score matching to determine the mean difference between variables in the treatment and control shows that a bantam but significant CSR interventions have been made by the MOCs in the areas that will discourage people from engaging in inter-communal violence. The findings suggest that an increase in CSR targeted at improving access to cultivatable land, enhanced fishing space, reducing multidimensional poverty, as well as reducing frustration and indignation; will dissuade local people from involvement in inter-communal violence.
Keywords: 330; Oil extraction communities; inter-communal violence; corporate social responsibility; Nigeria's Niger Delta